A207 POST-COLONOSCOPY COLORECTAL CANCERS IN ALBERTA: ROOM FOR QUALITY IMPROVEMENT. (1st March 2018) - Mohamed, M S; Sadowski, D; Johnson, D; Wong, C
Abstract: Background: Post-colonoscopy colorectal cancer (PCCRC) is an indicator of colonoscopy quality and can happen as a result of technical factors surrounding the procedure such as inadequate bowel preparation, incomplete examination, missed or partly resected early lesions and failure to adhere to follow-up guidelines. There is a gap in our knowledge of the prevalence and root causes of PCCRC in Alberta, which are essential for quality improvement interventions Aims: The aim of this study was to find out the prevalence and the factors associated with the development of PCCRC from a population based perspective. Methods: This study was carried out in Alberta, which has a population of 1.8 million people older than age 39. 100, 000 colonoscopies are done in the province annually. Centralized population-based data is available through the Alberta Cancer Registry (ACR), National Ambulatory Care Reporting System (NACRS), Discharge Abstract Database (DAD), and the Alberta Ambulatory Care Reporting System (AACRS). All initial cases of CRC appearing in the ACR during 2013 were linked to the NACRS, DAD and AACRS databases to determine dates and characteristics of all antecedent colonoscopies. Health record of the retrieved cases were reviewed. The study authors according to a structured algorithm reviewed an abstract of each case. Cases were classified according to a set of predetermined root causes Results: 1278 patients > 39 years of age were diagnosed with CRC in 2013 and had a colonoscopy identified by the database linkage. 146 CRC cases were diagnosed based on colonoscopy that was performed > 6 months but < 60 months after index colonoscopy. Cases were classified to root causes (See Table 1). A total of 71 colonoscopists had at least one missed cancer with one colonoscopist missed 5 cancers Conclusions: This study provides a rational basis for case exclusion as well as systematic categorization of PCCRC root causes. This approach can be used to obtain PCCRC data over longer periods of time and to get a more accurate estimate of its prevalence. The root causes identified in this study indicate that there is room for improvement in colonoscopy quality as well as for enhancement of clinical care pathways Funding Agencies: None